Pershing's crusaders : the American soldier in World War I (Modern war studies., 2017)
"The most systematic, comprehensive, detailed, and up-to-date study yet published of the experiences, daily life, and representative attitudes of the American soldier (Army & Marine) in World War I. It will be a seminal source for anyone interested in the World War I-era American army and/or the history of early twentieth-century America"--Publisher.